Big Data: Issues, Challenges, Technologies and Methods - Khalid, Adam; Fakhreldin, Mohammed Adam Ibrahim; Jasni, Mohamad Zain; Mazlina, Abdul Majid; Noraziah, Ahmad (2015)
With dramatically increase of emerging applications such as social media, sensors, videos and digital pictures data is become generating from everywhere. Due to characteristic of big data it becomes very difficult to Management, analysis, Storage, Transport and processing the data using the existing traditional techniques. This paper introduces several big data, Technologies and Methods. First introduction of big data, presented the Big Data Problem, Important of Big Data, Technologies and Methods of Big Data Management and Analyzed including Distributed File System, NOSQL Database, Hadoop/MapReduce, then Big Data Modelling, discuss the Big Data Security challenges, Finally, Future work and Conclusion .